Examining teachers' motivation in conducting teacher professional development: A self-determination theory perspective - Eko Purwanti; Salma Octavia (English Language Teaching Educational Journal, 2022)
Teacher Professional Development (TPD) can be referred as any activities that can improve the quality of teacher professionalism. This study aims to find out various activities of English Secondary School teachers regarding their teacher professional development and to investigate their motivation in conducting TPD based on Self-Determination Theory (SDT). Underpinned by qualitative approach, this research used descriptive qualitative research design. Three English Secondary School teachers were involved as the participants, and individual interviews were used to collect the data. The findings showed that TPD activities done by the participants were 1) attending workshop and seminar, 2) joining English Subject Teacher Forum, 3) having informal peer discussions, and 4) reading teaching resources. The next findings regarding the teachers’ motivation in conducting TPD proves that the three aspects of SDT emerged from the participants, comprising 1) self-awareness, 2) in line with profession, and 3) the need to be competent. These findings imply that various activities of TPD driven by internal motivation can be conducted by English Secondary School teachers. Therefore, it is recommended that teachers have internal motivation in order to carry out TPD.